Genetic Evolution and Implications of the Mitochondrial Genomes of Two Newly Identified Taenia spp. in Rodents From Qinghai-Tibet Plateau - Wu, Yao-Dong; Li, Li; Fan, Yan-Lei; Ni, Xing-Wei; Ohiolei, John Asekhaen; Li, Wen-Hui; Li, Jian-Qiu; Zhang, Nian-Zhang; Fu, Bao-Quan; Yan, Hong-Bin; Jia, Wan-Zhong (Frontiers in Microbiology, 2021)
The larva of Taeniidae species can infect a wide range of mammals, causing major public health and food safety hazards worldwide. The Qinghai-Tibet Plateau (QTP), a biodiversity hotspot, is home to many species of rodents, which act as the critical intermediate hosts of many Taeniidae species. In this study, we identified two new larvae of Taenia spp., named as T. caixuepengi and T. tianguangfui, collected from the plateau pika (Ochotona curzoniae) and the Qinghai vole (Neodon fuscus), respectively in QTP, and their mitochondrial genomes were sequenced and annotated. Phylogenetic trees based on the mitochondrial genome showed that T. caixuepengi has the closest genetic relationship with T. pisiformis, while T. tianguangfui was contained in a monophyletic group with T. crassiceps, T. twitchelli and T. martis. Biogeographic scenarios analysis based on split time speculated that the speciation of T. caixuepengi (~5.49 Mya) is due to host switching caused by the evolution of its intermediate host. Although the reason for T. tianguangfui (~13.11 Mya) speciation is not clear, the analysis suggests that it should be infective to a variety of other rodents following the evolutionary divergence time of its intermediate host and the range of intermediate hosts of its genetically close species. This study confirms the species diversity of Taeniidae in the QTP, and speculates that the uplift of the QTP has not only a profound impact on the biodiversity of plants and animals, but also that of parasites.